Acceptance analysis of using google classroom with the UTAUT method in online learning - Ramdani, Fitri; Priyanto, Priyanto (Jurnal Pendidikan Teknologi dan Kejuruan, 2024)
The use of Google Classroom, which is less than optimal when the online learning process takes place, requires analysis to find out what factors influence the acceptance of using Google Classroom at SMK Negeri 3 Mataram. One technology acceptance model often used is the Unified Theory of Acceptance and Use of The Technology (UTAUT). The main variables of UTAUT in this study consist of six variables, namely Performance Expectancy, Effort Expectancy, Social Influence, Facilitating Conditions, Behavioral Intentions, Use Behavior, and two additional variables, namely Attitude Toward using Technology and Computer Self-Efficacy. Data was collected using a questionnaire distributed to class XII SMK Negeri 3 Mataram. The data was then analyzed using two methods, namely, the outer model and the inner model. After that, bootstrapping is done to get the path coefficient value as the basis for significant testing. The results showed that the factors that influence the level of acceptance of using Google Classroom at SMK Negeri 3 Mataram are Social Influence on Behavioral Intention, Facilitating Conditions on Behavioral Intention, Facilitating Conditions on Use Behavior, Computer Self-Efficacy on Performance Expectancy, Computer Self-Efficacy on Effort Expectancy, Performance Expectancy on Attitude Toward using Technology, Effort Expectancy on Performance Expectancy, Attitude Toward using Technology has a significant effect on Use Behavior, Computer Self-Efficacy on Use Behavior.